Identification of Milkfish Supply Chain in PT XYZ at Semarang City, Central Java Province - Romdhon, M Mustopa; Asmarani Nurshabrina,; Melli, (Indonesian Journal of Agricultural Research, 2019)
Bandeng Presto is one of the typical foods of Semarang City, one of the famous milkfish processing industries is PT XYZ. This study aims to identify milkfish supply chains at PT XYZ in Semarang City. The collection of primary and secondary data was carried out in January-February 2019, which was used in describing the supply chain flow. The method of data analysis uses descriptive qualitative. The results obtained are 2 patterns of supply chain flow, the flow I pattern consists of companies - suppliers as well as farmers and flow patterns II consisting of companies - suppliers - farmers. The activities of each pattern are explained in the flow of product, information, and financial.